Petrous Apicitis: A Systematic Review and Case Presentation. Issue 7 (August 2022) - Talmor, Guy; Vakil, Mayand; Tseng, Chris; Svider, Peter; Ying, Mary; Eloy, Jean Anderson
Abstract : Introduction: Petrous apicitis (PA) is a rare but dangerous complication of acute otitis media. The objective of this study is to present a case of PA and systematically review the existing literature on PA to characterize clinical presentation, diagnosis, management, and outcomes in the antibiotic era. Methods: A comprehensive search from 1983 to June 1, 2020, of PubMed, MEDLINE, Cochrane Library, and EmBase databases was conducted. Studies with clinical data regarding patients with PA were included. Non-English literature or studies with insufficient individual patient data were excluded. Sixty-seven studies were included with a total of 134 patients. Results: A total of 67 articles were found to meet criteria for inclusion. The mean age of presentation was 33 years. Recent acute otitis media was reported in 78 patients (58.2%). Only 3 patients (2.2%) were immunocompromised, and 8 patients (6.0%) had a history of diabetes. Gradenigo's triad of abducens palsy, otorrhea, and retro-orbital or facial pain was reported in 28 patients (20.9%); however, these presenting symptoms were common individually (51.5%, 48.5%, and 64.2%, respectively). Hearing loss (35.8%), facial weakness (17.9%), and vertigo (7.5%) were also reported. The most frequently cultured pathogen was Pseudomonas (34.2%), followed by Streptococcus and Staphylococcus . All 134 patients underwent imaging, with computed tomography being the most frequently used modality (56.0%). Nearly all patients received antibiotic therapy (95.6%), with 91 (67.9%) undergoing surgery ranging from myringotomy (26.9%) to petrosectomy (25.4%). Five patients (5.7%) died because of complications related to PA. Mean follow-up was 11.0 months. Conclusions: Petrous apicitis has a variable presentation with potential for severe morbidity. Mortality rates are low, and presentation with Gradenigo's triad is uncommon. Appropriate medical management with surgical drainage can avoid long-term sequelae.